Badminton Competition Aplication Using Website - Nyimas Sopiah; Devrhi Setiawan (Journal of Information System and Informatics, 2020)
Persatuan Bulu Tangkis Seluruh Indonesia (PBSI) is an organization that manages the game of badminton in Indonesia. The Palembang branch of PBSI has so far held a competition that has not used special software, from registration to the results of the competition. The problem that often occurs is the frequent occurrence of misinformation about the race. For this reason, an application will be made that can help accommodate the race administration, starting from the registration of the race to the results of the race. Application created using the website. The development method used in making applications is the Web Engineering method. The programming language used is using PHP and the database is used using MySql. The results of this study are expected to make it easier for athletes to see information about race events, match schedules, race registration, making it easier for badminton clubs to register their athletes in competitions held by PBSI